A comparison of the quality control systems employed by sub-contracting companies in the garment industry - Vidal, Benjamina Madueno; Dizon, Angelita Mendoza (1993.)
Quality control system is define as the step by step procedure and standards adhered to by the company in order to achieve good quality. This study was solely undertake to investigate and compare the quality control system set and applied by 10 garment sub-contracting companies in the Metro Manila area. The objective of the study were : a0 to determine is sub-contactors have st their own quality control system which they follow in producing items : and to determine the different quality control systems that sub-contractors use. Questionnaires were sent to the sub-contracting companies. Out of the 30 questionnaires sent, eleven companies responded and ten were chosen as samples to represent the sub-contractors in the Metro Manila area. The results showed that garment sub-contractors did have their own quality control standards and procedures. Although, they did not have exactly the same procedures in quality control as they did not have exactly the same procedures in quality control as they differ in the job orders that they accept and their experiences in handling their orders, there are similarities in their systems and standards. But it will be noted that a number of them were more critical and more organized than others especially the large scale companies. The system that they employ revolves mainly on inspection and this is done by the buyer's inspector aside from their own personnel. Their standards are based on the buyer's specification aside from being developed from their own experience in handling the item.
Special Problem (BS Clothing Technology)--University of the Philippines Diliman.
Keywords: Clothing factories -- Philippines -- Quality control; Clothing factories -- Philippines -- Subcontracting